Territorial Patterns of Innovation in Europe - Roberta Capello; Camilla Lenzi (European Regional Science Association (ERSA), 2011)
This paper investigates over the way in which regions innovate. The conceptual framework departs from the simple idea that scientific activities equates knowledge, assuming that the presence of local knowledge produced by research centers, universities and firms was a necessary and sufficient condition for increasing the innovative capacities in local firms, fed by local spillovers. In particular, the paradigmatic jump in interpreting regional innovation processes lies in a conceptual framework interpreting not a single phase of the innovation process, but the different modes of performing the different phases of the innovation process, highlighting the context conditions (internal and external to the region) that accompany each innovation pattern. The paper conceptually identifies different territorial patterns of innovation, and empirically test their existence in Europe. Interesting results emerge from the European territory, witnessing the existence of large differences in the territorial patterns of innovation. These results strongly support normative suggestions towards thematically/regionally focused innovation policies.
Keywords: 330